Controlled Drug Delivery Systems Towards New Frontiers in Patient Care - Rossi, Filippo; Perale, Giuseppe; Masi, Maurizio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers a state-of-the-art overview of controlled drug delivery systems, covering the most important innovative applications. The principles of controlled drug release and the mechanisms involved in controlled release are clearly explained. The various existing polymeric drug delivery systems are reviewed, and new frontiers in material design are examined in detail, covering a wide range of polymer modification techniques. The concluding chapter is a case study focusing on use of a drug-eluting stent. The book is designed to provide the reader with a complete understanding of the mechanisms and design of controlled drug delivery systems, and to this end includes numerous step-by-step tutorials. It illustrates how chemical engineers can advance medical care by designing polymeric delivery systems that achieve either temporal or spatial control of drug delivery and thus ensure more effective therapy that eliminates the potential for both under- and overdosing.
Introduction: chemical engineering and medicine -- Principles of controlled drug release: a mass transport matter -- Overview on polymeric drug delivery systems -- Device design: functional polymers for drug delivery -- Case study: drug eluting stent.
Keywords: Biomedical engineering; Chemistry, Technical; Biomaterials; Industrial engineering; Production engineering; Pharmaceutical chemistry; Biomedical Engineering and Bioengineering; Industrial Chemistry; Biomaterials; Industrial and Production Engineering; Pharmaceutics